Industrial training report: Pusat Khidmat Rakyat Parlimen Masjid Tanah - Md Hartika, Muhammad Hasif (Faculty of Business and Management, 2025)
In the following paragraphs, I intend to narrate the story of my internship at Pusat Khidmat Rakyat Parlimen Masjid Tanah Melaka which started on 12 August 2024 and ended on the 24th of January 2025. This internship is undertaken to complete my degree in Business Administration (Hons) International Business. In this report, I have outlined pertinent information relating to the organization, especially the department in which I did my internship based on my experiences during my internship. I was also able to obtain all the information about the organization as well as the department by interviewing the staff as well as searching for it on the portal. As part of my report, I have also included the practical side of my internship. It was conducted through my observations of the organization’s internal environment. At the end of my report, based on the analysis I made, I wrote the recommendations and included a photo of what I did during my internship.